2000
DOI: 10.1159/000054518
|View full text |Cite
|
Sign up to set email alerts
|

Perimembrane Localization of the Estrogen Receptor α Protein in Neuronal Processes of Cultured Hippocampal Neurons

Abstract: There is clear evidence of rapid, nongenomic responses to estrogen in a variety of neuronal model systems. To address the question of whether some of these rapid estrogen signals might be transduced by the classical estrogen receptor (ER) α or a closely related protein in nontransformed neurons, we undertook the present study using isolated fetal rat hippocampal neurons. Several antibodies developed to detect ERα were tested in this system and showed positive membrane staining in nonpermeabilized neurons. MC-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 32 publications
8
69
0
Order By: Relevance
“…The intensity of staining qualitatively varied among the neurons in our dispersion cultures. Our results corroborate previous findings that hippocampal neurons express extranuclear ER-␣ (Clarke et al, 2000;Milner et al, 2001;Adams et al, 2002;Kalita et al, 2005;Romeo et al, 2005) and extranuclear ER-␤ (Mitra et al, 2003;Kalita et al, 2005;Milner et al, 2005). We focused specifically on cultured hippocampal neurons expressing the NR1 protein and analyzed the pattern and distribution of the punctate extranuclear immunostaining of ER proteins present along dendrites.…”
Section: Nr1 and Vglut1 Synaptic Protein Distribution Significantly Csupporting
confidence: 89%
See 1 more Smart Citation
“…The intensity of staining qualitatively varied among the neurons in our dispersion cultures. Our results corroborate previous findings that hippocampal neurons express extranuclear ER-␣ (Clarke et al, 2000;Milner et al, 2001;Adams et al, 2002;Kalita et al, 2005;Romeo et al, 2005) and extranuclear ER-␤ (Mitra et al, 2003;Kalita et al, 2005;Milner et al, 2005). We focused specifically on cultured hippocampal neurons expressing the NR1 protein and analyzed the pattern and distribution of the punctate extranuclear immunostaining of ER proteins present along dendrites.…”
Section: Nr1 and Vglut1 Synaptic Protein Distribution Significantly Csupporting
confidence: 89%
“…ER-␣ and ER-␤ have been found at extranuclear sites in the hippocampus and cortex (Dubal et al, 2006). Their presence in dendritic spines and axons of hippocampal and cortical neurons (Clarke et al, 2000;Adams et al, 2002;Kalita et al, 2005;Romeo et al, 2005;Hu et al, 2007) suggests a role for the ER as a transducer of rapid, nongenomic estrogen-mediated events during synapse formation.…”
Section: Introductionmentioning
confidence: 99%
“…Our ERα localization data in NLT neurons corresponds with other groups in that "classical" ERs are positioned not only in the nucleus, but in the cytoplasm and outgrowths as well (Clarke, 2000;Hart, 2007) where they are available to interact with cytoplasmic signaling cascades. Immunofluorescence and cell fractionation showed that E2-induced αCaMKII autophosphorylation in NLT neurons occurs specifically in the cell body and processes, suggesting that the extranuclear pool of ER is responsible for mediating this event.…”
Section: Discussionsupporting
confidence: 85%
“…These studies have revealed that classical nuclear ERs are located at the plasma membrane of a variety of cell types, including endothelial cells, spermatozoa, and neurons in the brain (Pappas et al, 1995;Clarke et al, 2000), hence proving that membrane estrogen signaling through nuclear receptors is a more common phenomenon than originally thought. However, an issue that should be addressed is which of the nuclear ERs is responsible for the rapid events of membrane signaling and how it is connected to E 2 -mediated signal transduction systems.…”
Section: Discussionmentioning
confidence: 96%